Examining Islamic Pro-Social Instruments in the Context of Indonesian Givers' Happiness (ZISWAF: Jurnal Zakat dan Wakaf, 2023)
Giving or helping others can bring happiness and satisfaction to the giver. Participation in pro-social activities, such as donating to those in need, can increase happiness and satisfaction. This research explores the relationship between pro-social activities and subjective happiness in Indonesia, using data from the Indonesian Family Life Survey batch 5. By estimating a logistic model and calculating marginal effects, we assess this relationship. The results show a positive correlation between the amount of donation given and individual happiness levels. Additionally, income per capita and marital status have a positive association with happiness. Specifically, married individuals report higher levels of happiness than unmarried or divorced individuals. These findings have important implications for policymakers, particularly those involved in pro-social initiatives, such as the Ministry of Religion, BAZNAS, and the Indonesian Waqf Board. They suggest that promoting pro-social activities and policies supporting family formation and economic stability can increase happiness levels in Indonesian society. The Amil Zakat Institute, a stakeholder institution in Ziswaf funds management, can utilize this research to enhance the well-being of recipients and improve their standard of living. Furthermore, employing pro-social modeling through two-stage regression reveals that subjective well-being, measured by the monetary-based natural logarithm of consumer expenditure, can serve as a proxy for happiness associated with individual characteristics. These findings highlight that individual characteristics, specifically marital status, impact happiness levels. Further research could focus on examining specific types of donations to gain a deeper understanding of their respective effects on happiness.